2008
DOI: 10.1080/13813450802033990
|View full text |Cite
|
Sign up to set email alerts
|

Arterial smooth muscle cells dysfunction in hyperglycaemia and hyperglycaemia associated with hyperlipidaemia: from causes to effects

Abstract: Given the important role of smooth muscle cells in arterial wall dysfunction in diabetes, as well as in diabetes associated with accelerated atherosclerosis, we provide a brief review of the recent achievements in identification of signalling molecules underlying their altered cellular responses, and examine the consequences of these pathological insults on smooth muscle cells properties. The original results emerging from the Golden Syrian hamster model (rendered diabetic or simultaneously hyperlipidaemic-dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The mechanisms that underlie diabetic vascular disorders are multifactorial. Besides endothelium dysfunction, abnormal smooth muscle function also critically contributes to vascular pathology in diabetes, especially under the long-term conditions of glucotoxicity and lipotoxicity (49). A major cause of diabetic BK channel abnormality is attributed to the downregulation of BK-␤1 expression in vascular SMCs (26, 27), resulting in impaired BK channel sensitivity to Ca 2ϩ and voltage activation (26, 27).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms that underlie diabetic vascular disorders are multifactorial. Besides endothelium dysfunction, abnormal smooth muscle function also critically contributes to vascular pathology in diabetes, especially under the long-term conditions of glucotoxicity and lipotoxicity (49). A major cause of diabetic BK channel abnormality is attributed to the downregulation of BK-␤1 expression in vascular SMCs (26, 27), resulting in impaired BK channel sensitivity to Ca 2ϩ and voltage activation (26, 27).…”
Section: Discussionmentioning
confidence: 99%
“…Increased proliferation and migration of VSMCs aggravates the progression of atherosclerosis by converting a fatty streak to an irreversible blood plaque [11]. Several studies have demonstrated that the vascular complications caused by hyperglycemia results from abnormal proliferation and migration of VSMCs [32,33,34] causing DM induced atherosclerosis [34].…”
Section: Discussionmentioning
confidence: 99%